Pemberdayaan Masyarakat Melalui Pelatihan Digital Marketing Sebagai Upaya Mendukung Potensi UMKM Desa Bedayu, Kecamatan Senduro, Kabupaten Lumajang - Fidyah Jayatri; Dwi Yanuarindah Putri; Fahmi Abdul Halim; Roni Wiranata; Siti Aisyah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Observational findings indicate that most tourism MSMEs in Bedayu Village, Senduro, are not yet skilled in optimal digital marketing. Lack of knowledge about content creation, business account management, and online marketing strategies means that the vast promotional opportunities through the digital world are not fully utilized. Therefore, special mentoring is needed that focuses on mastering digital skills, such as simple website creation, social media optimization, and data-driven online marketing strategies through a community service program (PKM) in collaboration with KKN students in Bedayu Village. The purpose of this program is to increase competitiveness, expand the reach of regional tourism promotions, and improve the welfare of the Bedayu Village community. The use of digital technology is also in line with the direction of creative economic development and sustainable tourism, which emphasizes innovation, independence, and community empowerment based on the potential of Bedayu Village MSMEs.